Intelligent Art Toy Interaction for Stress Management: A Multimodal Biofeedback Approach - Li, Xin (2025 IEEE 3rd International Conference on Image Processing and Computer Applications (ICIPCA), 2025)
This research pioneers a novel stress intervention framework through the fusion of interactive technology and therapeutic art toys. A plush prototype embedded with flexible intronic sensors continuously monitors cardiac activity, translating real-time heart rate fluctuations into dynamic LED light patterns. This tactile-visual feedback loop allows users to intuitively regulate stress responses via multisensory engagement. In a randomized controlled trial (N=45), the experimental group using the interactive system demonstrated clinically meaningful improvements: heart rate variability (SDNN) increased by 26.7 % alongside a 9.5 % heart rate reduction, whereas controls showed negligible changes. Physiological analysis confirmed a strong inverse HRV-heart rate correlation, aligning with autonomic nervous system homeostasis mechanisms. The system's efficacy stems from three innovations: 1) Miniaturized biosensing enabling unobtrusive physiological monitoring; 2) Gamified biofeedback transforming stress regulation into intuitive sensory interaction; 3) Artistic embodiment reducing technology anxiety through culturally resonant forms. These findings validate intelligent art toys as viable non-pharmacological tools for stress mitigation, particularly among youth populations resistant to traditional interventions. By bridging affective computing with wearable biosensors, this work expands human-computer interaction paradigms beyond clinical settings into daily life. The prototype's scalable design supports diverse applications-from classroom stress management to workplace wellness programs-demonstrating how emotionally intelligent artifacts can democratize mental health support. Future iterations will enhance cross-cultural adaptability and investigate long-term neuroplasticity effects, ultimately advancing personalized digital therapeutics through aesthetic engagement.